2018
DOI: 10.1371/journal.pone.0198757
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis of oral microbiota and its association with salivary immunological biomarkers in autoimmune liver disease

Abstract: The gut microbiota has recently been recognized to play a role in the pathogenesis of autoimmune liver disease (AILD), mainly primary biliary cholangitis (PBC) and autoimmune hepatitis (AIH). This study aimed to analyze and compare the composition of the oral microbiota of 56 patients with AILD and 15 healthy controls (HCs) and to evaluate its association with salivary immunological biomarkers and gut microbiota. The subjects included 39 patients with PBC and 17 patients with AIH diagnosed at our hospital. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 54 publications
(45 reference statements)
4
66
0
2
Order By: Relevance
“…Some studies supported its beneficial effect on prognosis [257]. A Japanese study revealed that patients with PBC showed significant increases in Eubacterium and Veillonella and a significant decrease in Fusobacterium in the oral microbiota compared with the healthy controls [258]. In this report, the relative abundance of Veillonella was positively correlated with the levels of IL-1β, IL-8 and immunoglobulin A in saliva and the relative abundance of Lactobacillales in feces [258].…”
Section: Primary Biliary Cholangitis (Pbc)supporting
confidence: 54%
“…Some studies supported its beneficial effect on prognosis [257]. A Japanese study revealed that patients with PBC showed significant increases in Eubacterium and Veillonella and a significant decrease in Fusobacterium in the oral microbiota compared with the healthy controls [258]. In this report, the relative abundance of Veillonella was positively correlated with the levels of IL-1β, IL-8 and immunoglobulin A in saliva and the relative abundance of Lactobacillales in feces [258].…”
Section: Primary Biliary Cholangitis (Pbc)supporting
confidence: 54%
“…We found that the genus Prevotella was significantly more abundant in AG saliva. A similar finding was observed by Fan et al, who identified increased Prevotella in the oral microbiome of drinkers [113]. The observed differences in Prevotella among our groups may suggest a possible dysbiosis in the salivary microbiota of the alcohol users.…”
Section: Discussionsupporting
confidence: 92%
“…Leclercq et al identified the alcohol-induced dysbiosis of gut microbiota and subsequent inflammatory responses as the likely causes of depressive disorders and alcohol craving [16]. Similarly, variation in the human oral microbiome caused by alcohol use has been related to systemic inflammatory and autoimmune disorders [112,113]. We found that the genus Prevotella was significantly more abundant in AG saliva.…”
Section: Discussionmentioning
confidence: 52%
“…However, direct evaluation of the oral microbiome has not been performed in AIH. Our data indicated a significant increase in the abundance of the genus Veillonella in the oral microbiota of patients with AIH, and the abundance of the genus Veillonella was positively correlated with the levels of proinflammatory cytokines, such as IL -1β, IL -6, IL -8, and IL -12p70 in the saliva of patients with AIH 21) (Figure 1a). However, it is unknown whether the inflammatory state in the oral cavity of AIH patients is the cause or consequence of imbalances in the salivary microbiota and whether the oral cavity or the gut immune response exerts greater influence on the observed dysbiosis of the oral microbiota.…”
Section: Gut and Oral Microbiota In Aihmentioning
confidence: 71%
“…The relative abundance of Streptococcus was negatively correlated with the levels of IL -1β, IL -4, IL -6, IL -7, IL -8, IL -12p70, IL -17, G -CSF, IFNγ and TNFα, while the relative abundances of Veillonella and Prevotella/Porphyromonas were positively correlated with the IgA level in the saliva of patients with PBC. Moreover, the relative abundances of Neisseria and Eubacterium/Filifactor were positively correlated with the salivary cytokine levels in patients with PBC 21) .…”
Section: Gut and Oral Microbiota In Pbcmentioning
confidence: 90%